2017
DOI: 10.1002/clen.201600679
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mineral‐Based Amendments for Enhancing Phytostabilization in Lolium perenne L. Cultivation

Abstract: An experimental investigation is conducted to explore the suitability of Lolium perenne L., diatomite, chalcedonite, dolomite, and limestone for the phytostabilization of Ni and Cu in contaminated soil. A controlled greenhouse study is conducted. The soil is enriched with rising dose of Cu and Ni, that is, (0, 150, 250, and 350 mg kg À1) and (0, 150, 300, and 450 mg kg À1 ), respectively. The phytostabilization potential of perennial ryegrass is evaluated using a bioaccumulation coefficient and translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…According to Lee et al (2014), the plant species suitable for phytostabilization should be characterized by TF < 1. This findings are confirmed with numerous other studies, which have reported L. perenne to be a suitable species for the phytostabilization process (Norini et al 2019;Radziemska et al 2018). Zn was translocated more effectively than the other two metals in both of the amended treatments (Table 3).…”
Section: Translocation and Bioaccumulation Of Heavy Metalssupporting
confidence: 90%
See 1 more Smart Citation
“…According to Lee et al (2014), the plant species suitable for phytostabilization should be characterized by TF < 1. This findings are confirmed with numerous other studies, which have reported L. perenne to be a suitable species for the phytostabilization process (Norini et al 2019;Radziemska et al 2018). Zn was translocated more effectively than the other two metals in both of the amended treatments (Table 3).…”
Section: Translocation and Bioaccumulation Of Heavy Metalssupporting
confidence: 90%
“…It might be attributed to the absorption of the metal on the root surface which, consequently, limits the transport to the aboveground parts of the plant (Pogrzeba et al 2019). Radziemska et al (2018) reported a reduction of Cu concentration in the aboveground parts of L. perenne after the application of lime and diatomite to the soil. Moreover, a lower heavy metal concentration in the roots of the amended treatments may be associated with the mycorrhizal root colonization, especially that the ability of AMF to stabilize heavy metals by hyphae on the surface of the roots was previously reported (Wu et al 2016).…”
Section: Heavy Metal Concentration and Plant Biomass Productionmentioning
confidence: 99%
“…Urban green areas fulfill numerous functions, the more important being: the reduction of pollutants by phytoremediation [1,2,3] and the regulation of the urban microclimate [4]. On that basis, the concept of green infrastructure was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…The translocation factor is the ratio of the metal concentration in the shoots to that in the roots [40].…”
Section: Bcf = Metal Concentration In Shoot Metal Concentration In Soilmentioning
confidence: 99%